Analisis Pengaruh Asset Tangibility, Capital Expenditure, Dividend Payout Ratio, dan Institutional Ownership Terhadap Cash Holding pada Perusahaan Sektor Consumer Non-Cyclicals di Bursa Efek Indonesia - Erika Leony (MABIS, 2025)
The purpose of this study is to determine and analyze the influence of asset tangibility, capital expenditure, dividend payout ratio, and institutional ownership on cash holdings. This is a quantitative study with an associative approach. Data collection was conducted using documentation and literature review techniques. The subjects of this study were non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period, with a population of 129 companies. Using a purposive sampling approach, a sample of 27 companies was obtained and 135 data sets were collected. The data used were secondary data in the form of financial reports and annual reports of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange, obtained from www.idx.co.id and the company's official website. Data analysis was performed using SPSS version 26. The results indicate that asset tangibility and institutional ownership have a negative and significant effect on cash holdings. Meanwhile, the dividend payout ratio has a positive and significant effect on cash holdings. Capital expenditure has no significant effect on cash holdings.